The Role of Contemporary Fatwa in Preventing Religious Extremism and Radicalism - Muhammadong Muhammadong (Faculty of Teacher Training and Education, Palangka Raya University, Central Kalimantan, Indonesia. Pos Code 73112, 2025)
This research aims to analyse the function of contemporary fatwas in mitigating extremism and radicalism, providing insights into their efficacy within the current social and cultural milieu. The goal of this study is to help come up with innovative ways to deal with these threats. The growth of radicalism and religious fanaticism, especially in Muslim populations, is a menace to the whole world. Misreading religious scriptures and spreading radical ideas frequently lead to bloodshed, which makes things less peaceful. Fatwas, which are religious rulings made by Islamic experts, are very important for dealing with these problems. This qualitative study examines the function of fatwas in mitigating extremism and radicalism. It looks at fatwas given by well-known scholars and institutions in reaction to extremist ideology. It focuses on how these fatwas make it clear what the true understanding of Islam is and discourage radical beliefs. The results show how important fatwas are for spreading moderate, peaceful views of Islam and how important religious leaders are for leading communities towards tolerance and living together. The study indicates that fatwas can effectively inhibit the proliferation of extremism, contingent upon their issuance by reputable, competent scholars who prioritise peace in their interpretations. Tujuan dari penelitian ini adalah untuk menganalisis fungsi fatwa kontemporer dalam meredam ekstremisme dan radikalisasi, memberikan wawasan mengenai efektivitasnya dalam konteks sosial dan budaya saat ini. Penelitian ini bertujuan untuk membantu mencari cara inovatif dalam menangani ancaman-ancaman ini. Pertumbuhan radikalisasi dan fanatisme agama, terutama di kalangan populasi Muslim, menjadi ancaman bagi seluruh dunia. Penafsiran yang keliru terhadap teks-teks agama dan penyebaran ide-ide radikal sering kali berujung pada pertumpahan darah, yang mengurangi kedamaian. Fatwa, yaitu keputusan-keputusan agama yang dikeluarkan oleh ahli agama Islam, sangat penting dalam menangani masalah-masalah ini. Penelitian kualitatif ini mengkaji fungsi fatwa dalam meredam ekstremisme dan radikalisasi. Penelitian ini memeriksa fatwa-fatwa yang dikeluarkan oleh ulama dan lembaga terkemuka sebagai respons terhadap ideologi ekstremis. Fokusnya adalah bagaimana fatwa-fatwa tersebut menjelaskan pemahaman yang benar tentang Islam dan mencegah keyakinan radikal. Hasil penelitian menunjukkan betapa pentingnya fatwa dalam menyebarkan pandangan moderat dan damai tentang Islam serta peran penting pemimpin agama dalam membimbing komunitas menuju toleransi dan kehidupan bersama. Penelitian ini menunjukkan bahwa fatwa dapat secara efektif menghambat penyebaran ekstremisme, tergantung pada penerbitannya oleh ulama yang memiliki reputasi dan kompetensi, yang mengutamakan perdamaian dalam penafsirannya